Impact of crop varieties on household food security in Haor areas of Bangladesh - Kashem, MA; Farouque, MG; Roy, PC (International Journal of Agricultural Research, Innovation and Technology, 2014)
The purpose of the study was to identify the crop varieties in the Haor area of Netrokona district to minimize the food vulnerability situation during food crisis. The study was conducted in four selected villages of Madan and Khaliajuri Upazilas under the Netrokona district. Data were collected from randomly selected 400 farmers from the study area in the year 2011. The findings of the study revealed that farmers usually cultivate only three HYV boro rice varieties (BR 19, BRRI dhan 28 and BRRI dhan 29) in the Haor area under study. In aman season farmers mostly cultivate local varieties and they get minimum yield. Only few vegetables found to cultivate by the farmers in Haor area. The vegetables are: onion, garlic, chilli, bottle gourd, sweet gourd, ladys finger and tomato. Among these onion, garlic and chilli are mostly cultivated. Many farmers reported that during the flood they had to face serious problems in respect of communication, diseases, increased price of different commodities, and lack of adequate government safety net programs/relief. Farmers lack of flood preparedness has been observed while some farmers remained uncared about the occurrence of flood and consequently they did not take any preparedness for flood. DOI: http://dx.doi.org/10.3329/ijarit.v3i2.17812 Int. J. Agril. Res. Innov. & Tech. 3 (2): 7-11, December, 2013